Sociological portrait of the higher bureaucracy in Russia - G. A. Borshchevskiy (RUDN journal of Sociology)
The article considers the sociological aspects of the senior bureaucrats’ appointment in the Russian federal ministries in recent five years. The study aims at identifying the prevailing recruitment model and at assessing the efficiency of policies, the necessity of which is determined by the high influence of bureaucracy in the Russian society and by the negative reputation of the civil service. The theoretical framework of the study consists of the theories of bureaucracy by Max Weber, Karl Marx, and Michel Crozier. The predictor variables describe personal characteristics of senior executives and the mode of their recruitment. The author tested two hypotheses about the predominance of one of two higher bureaucrats’ recruitment models: patrimonial (political, patronage) or meritorious; the second model seems to prevail. Based on the Russian dataset, the author also examined the connection between the recruitment model of senior bureaucrats and the efficiency of ministries in implementing government programs, information openness and contribution to the national economic growth. In all three cases, ministries headed primarily by career (meritorious) bureaucrats turned out to be more effective. The primary data on 381 senior civil servants’ biographies obtained was collected from the personal pages of official ministerial websites with the method of content analysis. The data on the ministries’ efficiency was collected from the annual ministry reports, public indices of informational openness, reports about the state programs implementation, and economic input of each ministry in the sectoral GDP. Quantitative methods such as regression analysis and statistical analysis were used to interpret the data. The author concludes that the Russian system of governance needs a special body to administer its higher bureaucracy (recruitment, remuneration, payment, retirement, etc.) structurally resembling the senior civil service in the OECD countries.